MEMBANGUN KERUKUNAN MASYARAKAT MULTIKULTURAL - Ngainun Naim (Harmoni, 2016)
It is important to build the harmony in the livelihood among religious followers in Indonesia continuously. We can appreciate their valuable contribution through thought and real action. The idea of teologi kerukunan and fikih kerukunan has important meaning in daily life. The two concept became the basic of theory to implement the harmonious life in multicultural Indonesia society, both theoretically and practically.